A case study of the Philippine foundation of rural broadcasters and its role in development communication - Arceo, Ma. Arlyn L.
In 1981, three principal organizations of broadcasters and media men whose aim was to disseminate news to help in the development of rural areas and its folks got together to form one organization. This was the beginning of the Philippine Foundation of Rural Broadcasters (FRB). The objective of this study is to find out what the FRB is as an organization and determine its role in development communication.